Applying the Kalman filter particle method to strange and open charm hadron reconstruction in the STAR experiment - Ju, Xin-Yue; Leung, Yue; Radhakrishnann, Sooraj; Chaloupka, Petr; Dong, Xin; Fisyak, Yury; Federic, Pavol; Kisel, Ivan; Ke, Hong-Wei; Kocan, Michal; Margetis, Spyridon; Tang, Ai-Hong; et al. (Nuclear science and techniques, 2023)
We applied KF Particle, a Kalman Filter package for secondary vertex finding and fitting, to strange and open charm hadron reconstruction in heavy-ion collisions in the STAR experiment. Compared to the conventional helix swimming method used in STAR, the KF Particle method considerably improved the reconstructed $$Λ$$, $$Ω$$, and $$D^0$$significance. In addition, the Monte Carlo simulation with STAR detector responses could adequately reproduce the topological variable distributions reconstructed in real data using the KF Particle method, thereby retaining substantial control of the reconstruction efficiency uncertainties for strange and open charm hadron measurements in heavy-ion collisions.
Gesehen am 08.12.2023